Model Mentoring Teachers and Parents as an Efforts for Brushing Teeth Behavior in Preschool Children - Tedi Purnama1 , Ngatemi1 , Indrayati Fadjeri1 , Rini Widiyastuti1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The dental health problems of preschool children are higher compared to primary schools, this is due tochildren not being able to do independent activities in brushing their teeth. The teacher and parent mentoringmodel is a model of learning to brush teeth in an effort to form the behavior of preschool brushing teeth witha period of 10 days. Methods: This study is the Research and Development (R & D) and test the model usingexperimental quasy pretest and posttest with control group design. Preschoolers research subjects weredivided into 2 groups: 1. Intervention model of mentoring teachers and parents brushing teeth 2. Model 21days as the control. Data were tested using intraclass correlation coefficient tests, repeated measures anova,friedman, t-test and mann whitney. Results: The application of the teacher and parent mentoring modelwas equally effective with the 21-day brushing model for improved tooth-brushing skills (p> 0.304) andequally effective for increasing plaque-free scores (p <0.788) compared to the control group. Conclusion:The application of the teacher and parents mentoring model effectively as efforts to establish the behaviorof preschool children brushing teeth.